Exploring Salvia miltiorrhiza’s Therapeutic Effects on Adenomyosis by Inhibiting TNF-α/HIF-1α/IL-17-Driven Inflammatory Cascade: Mechanistic Insights from Target Prediction and Experimental Validation - Yang Q; Hong J; Zheng X; Liu X; Lin H; Chen L; Zhong F; Zhang Q; Jiang J; Sun P (Journal of Inflammation Research)
Qiaomei Yang,1,* Jingxuan Hong,2,3,* Xinye Zheng,1,* Xianhua Liu,4 Hao Lin,1 Li Chen,1 Fuchun Zhong,5 Qianhui Zhang,1 Junying Jiang,1 PengMing Sun1 1Department of Gynecology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, 350001, People’s Republic of China; 2Department of Cardiology, Fujian Provincial Hospital, Provincial Hospital Affiliated to Fuzhou University, Fuzhou, Fujian, 350001, People’s Republic of China; 3Department of Cardiology, Provincial Clinical Medical College of Fujian Medical University, Fuzhou, Fujian, 350001, People’s Republic of China; 4Department of Pathology, Fujian Maternity and Child Health Hospital College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, 350001, People’s Republic of China; 5Department of Laboratory Medicine, Fujian Maternity and Child Health Hospital Affiliated to Fujian Medical University, Fuzhou, Fujian, 350001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junying Jiang, Email jiangjyf53@163.com PengMing Sun, Email fmsun1975@fjmu.edu.cnBackground: Adenomyosis is a chronic inflammatory gynecological disorder closely linked with diminished fertility potential that poses significant challenges in pharmacological management. Salvia miltiorrhiza (Danshen, DS), a traditional Chinese herb with proven anti-inflammatory properties, has shown efficacy in treating chronic inflammatory conditions across multiple organ systems. However, its mechanisms in addressing adenomyosis remain unclear.Methods: Ultra-performance liquid chromatography coupled with Q Exactive™ HF-X mass spectrometry (UPLC-QE-MS) was employed to identify the constituents of DS. Targets for DS in treating adenomyosis were identified from various databases and a PPI network was constructed. Core target genes were identified by Module analysis using MCODE and CytoNCA plugin of Cytoscape. Functional analyses of core target genes were performed using GO and KEGG, followed by molecular docking, transcriptomics validation, and molecular dynamics simulations. Predicted targets and pathways were validated through Western blotting, qRT-PCR, and IF.Results: Thirty-five potential bioactive components from ingredients absorbed into the bloodstream (IAIBs) of DS were identified. Network pharmacology predicted that DS might exert therapeutic effects on adenomyosis by modulating the TNF-α/IL-17/HIF-1α signaling pathways through key targets, including TNF, IL1β, MMP2, ESR1, PTGS2, STAT3, BCL2, AKT1, MMP9, and EGFR. Molecular docking demonstrated that the active components have strong affinities with these core targets. Transcriptomic profiling identified TNF and IL-1β as key therapeutic targets in DS-adenomyosis. Molecular dynamics simulations exhibited that the active components form stable conformations with the inflammation-related therapeutic targets TNF and IL-1β. In vivo showed that DS significantly improved pathological changes in adenomyosis mice by haematoxylin-eosin staining. Molecular assays demonstrated that DS decreased mRNA and protein expression of TNF-α, IL-17A, IL-1β, and HIF-1α.Conclusion: This study initially emphasizes the potential of DS in addressing adenomyosis by concurrently targeting an anti-inflammatory network involving the TNF-α/HIF-1α/IL-17 signaling pathways, supporting its development as a phytotherapeutic agent.Keywords: adenomyosis, Salvia miltiorrhiza, drug repurposing, network pharmacology, computational analysis, multi-target, anti-inflammation pathways